TAX FRAUD PHENOME: QUALIFICATION DUE TO CRIMINAL LAW IN FIELD OF VAT - Švecova, Ļubova (Administrative and Criminal Justice, 2016)
In the present article the author has considered in a concentrated form the essence of the tax fraud phenomenon, the responsibility for which is determined by the legislation, both in administrative and criminal order – in accordance with 218 (tax avoidance) and 177 (fraud) acts. The aim of the present research is to consider the problems of tax violation, to systematize the issues related to the qualification of criminal acts in the area of taxation at establishing the fact of fraud with value added tax. The author systematized the elements of criminal acts’ compounds - fraud and tax evasion, the importance of the aspect of separating fictitious and real transactions during their classification, as well as addressed issues related to the offense ascertaining at the stage of its ending, in case of fraud with value added tax. There have been no previous investigations found on researching the phenomenon of tax fraud in Latvia through the prism of analysis of prevalence cause, types on manifestation of the phenomenon and ways of preventing and dealing with it. While researching the phenomenon of tax fraud, the author intends to examine the problem in greater details. The main conclusion, which relates to fraud with value added tax, is the fact that the Law system on Value Added Tax itself enables the unfair taxpayer to commit fraud. The lack of clear approach and criteria for the qualification of tax fraud has a negative impact on the effectiveness of preventing and dealing with this criminal act.